1985
DOI: 10.1002/abio.370050108
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of enzymatic degradation of cellulose by application of mixed enzyme systems of different fungal origin

Abstract: Individual culture supernatants of six cellulolytic fungi and their mixed enzyme systems were compared in hydrolysis of pure celluloses and cellulose‐rich wastes. It has been observed that the hydrolysis rate of pure cellulosie substances in general increased by mixed enzymes as compared to the enzymes supernatant derived from only one microbial source. This effect was particularly high when Trichoderma and Penicillium enzyme systems were operated together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…These results are consistent with previous reports that the cellulase system in fungi includes three major hydrolytic enzymes: (a) an endocellulase that cleaves β-linkages at random; (b) a cellobiohydrolase, which releases cellobiose from either the reducing or the nonreducing end of cellulose; and (c) a β-glucosidase that releases glucose from cellobiose and short-chain cellooligosaccharides , . The low level of β-glucosidase activity was consistent with previous reports that Trichoderma reesei cellulases exert low β-glucosidase activity , ). It has also been reported that Trichoderma cellulases additionally contain at least three endoxylanases, and these enzymes might contribute to the xylanase activity in the C013L preparation.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous reports that the cellulase system in fungi includes three major hydrolytic enzymes: (a) an endocellulase that cleaves β-linkages at random; (b) a cellobiohydrolase, which releases cellobiose from either the reducing or the nonreducing end of cellulose; and (c) a β-glucosidase that releases glucose from cellobiose and short-chain cellooligosaccharides , . The low level of β-glucosidase activity was consistent with previous reports that Trichoderma reesei cellulases exert low β-glucosidase activity , ). It has also been reported that Trichoderma cellulases additionally contain at least three endoxylanases, and these enzymes might contribute to the xylanase activity in the C013L preparation.…”
Section: Discussionsupporting
confidence: 92%
“…A synergistic influence of the various enzymes in microbial cellulase complexes has been demonstrated (Szaká cs- Dobozi et al, 1985). Other researchers (McQueen and Van Soest, 1975;Bughrara et al, 1992) have reported an increase in the amount of neutral detergent residue solubilized by a mixture of cellulase and hemicellulase, compared to the solubilization achieved with the cellulase preparation alone.…”
Section: Discussionmentioning
confidence: 95%